Exploring Factors Affecting the Purchase Intention of Halal Food Products : An Empirical Study on Student Consumers - Purwanto, Agus; Sudargini, Yuli (IJOSMAS, 2021)
The purpose of this study is analyze the relationship of brand image, Food safety, Halal awareness,halal certificate and Halal marketing on purchase intention of halal food product. The method used in this research is quantitative method, data collection methods by distributing questionnaires to 120 halal food consumers in Indonesia. The method for processing data is by using PLS and using the SmartPLS version 3.0 software as a tool. The population in this study are consumers in Indonesia The questionnaire was distributed electronically using simple random sampling technique. The results showed that the variables of halal awareness, health, and perceived value showed a significant and positive influence on purchase intention. This shows the increasing awareness of consumers about the halalness of products, brand image,food safety affects purchase intention of halal food product, halal awareness affects purchase intention of halal food product,halal certificate affects purchase intention of halal food product, halal marketing affects purchase intention of halal food product, which increasingly encourages consumer interest to buy halal food products.